The role of nusantara ulama’s da’wah in islamic moderation: A critique of blackwater and peripheral in Islamic studies - Sa’dullah, Sa’dullah; Hajam, Hajam (Jurnal Ilmu Dakwah, 2025)
Purpose - This study aims to analyze the role of Nusantara ulama’s da’wah in promoting Islamic moderation as a response to global narratives that often marginalize peripheral Islamic traditions, as represented by the Blackwater symbol. Method - This research employs a qualitative approach using the library research method. Data were collected from various literature sources and analyzed descriptively and analytically. Result  -  The findings indicate that Nusantara ulama play a significant role in fostering Islamic moderation by integrating Islamic values with local wisdom. Nusantara Islam, characterized by its tolerance, inclusiveness, and flexibility, has proven to be a relevant model for Islamic moderation in global discourse. The narrative of Nusantara Islam addresses critiques of the marginalization of Southeast Asia as "peripheral Islam". It demonstrates that Islam can develop peacefully through processes of vernacularization and indigenization without losing its universal essence. Implication – This study underscores the importance of strengthening the study of Nusantara Islam in global discourse to offer an alternative to Islam's often conflictual and homogenizing narratives. Originality/Value - This research contributes by linking the da’wah of Nusantara ulama and the concept of Islamic moderation with critiques of global symbolism, such as Blackwater. *** Tujuan - Penelitian ini bertujuan untuk menganalisis peran da’wah ulama Nusantara dalam mempromosikan moderasi Islam sebagai respons terhadap narasi global yang seringkali mengabaikan tradisi Islam di pinggiran, sebagaimana diwakili oleh simbol Blackwater. Metode - Penelitian ini menggunakan pendekatan kualitatif dengan metode penelitian perpustakaan. Data dikumpulkan dari berbagai sumber literatur dan dianalisis secara deskriptif dan analitis. Hasil  -  Temuan menunjukkan bahwa ulama Nusantara memainkan peran penting dalam memajukan moderasi Islam dengan mengintegrasikan nilai-nilai Islam dengan kebijaksanaan lokal. Islam Nusantara, yang ditandai dengan toleransi, inklusivitas, dan fleksibilitas, telah terbukti menjadi model yang relevan untuk moderasi Islam dalam diskursus global. Narasi Islam Nusantara menanggapi kritik terhadap marginalisasi Asia Tenggara sebagai “Islam periferal”. Ia menunjukkan bahwa Islam dapat berkembang secara damai melalui proses vernacularisasi dan indigenisasi tanpa kehilangan esensi universalnya. Implikasi – Penelitian ini menekankan pentingnya memperkuat studi Islam Nusantara dalam diskursus global untuk menawarkan alternatif terhadap narasi Islam yang seringkali konflik dan homogenisasi. Orisinalitas/Nilai – Penelitian ini berkontribusi dengan menghubungkan dakwah ulama Nusantara dan konsep moderasi Islam dengan kritik terhadap simbolisme global, seperti Blackwater.